Strategie komunikacyjne minimalnie werbalnych dzieci rozpoczynających edukację przedszkolną - Kaźmierczak, Monika (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
In the so-called minimally verbal, a negligible degree of expressing communication behavior is diagnosed, which significantly reduces participation in interaction and reduces the effectiveness of communication. The minimal-verbal communication behaviors of preschool children in interaction are characterized by: sub-competence and transitional competence. With a shortage of linguistic resources, the child has specific communication behaviors, i.e. strategies that involve participation in interaction, the process of receiving and decoding meanings, and to a large extent the production and transmission of a message that is as understandable to the environment as possible. With limited language tools, children entering preschool education either withdraw from communicating or look for any possible means of interaction –both strategies can be observed in both natural and simulated pedagogical situations. The minimum verbosity of pre-school children does not exclude the possibility of interaction with other communication partners. The gradual transition from the level of sub-competency and transitional competence to a higher level requires early therapeutic and pedagogical activities, incentives to use achievement strategies more often, and to build bridges between communicative, linguistic and cultural competences. Without therapy, the strategies used may lead to fossilization, i.e. inhibit communication and the development of linguistic competence.